2010
DOI: 10.4067/s0718-19572010000200016
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos alimenticios del lenguado panámico Cyclopsetta panamensis (Paralichthyidae) en el Sureste del Golfo de California

Abstract: The feeding habits of the Panamic flounder Cyclopsetta panamensis caught in the SE Gulf of California were studied. The specimens were collected by demersal fish surveys during the years 2004-2008. The panamic flounder is a predator focusing mainly on crustaceans inhabiting the bottom belonging to Squillidae and Penaeidae. The diet of the Panamic flounder did not vary significantly according to depth or sex, and not size related variations in the diet composition were observed. Based on the TROPH value, the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Furthermore, these zones serve as transit areas for the predators of penaeids. Local studies have reported predator species such as swimming crabs of the genus Callinectes and fishes, such as the snooks Centropomus robalito and C. nigrescens; the flounder Cyclopsetta panamensi; the catfish Ariopsis seemani; the snappers Lutjanus argentiventris and L. novemfasciatus; and the milkfish Chanos chanos (Sepúlveda-Medina 1981, Amezcua andPortillo 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these zones serve as transit areas for the predators of penaeids. Local studies have reported predator species such as swimming crabs of the genus Callinectes and fishes, such as the snooks Centropomus robalito and C. nigrescens; the flounder Cyclopsetta panamensi; the catfish Ariopsis seemani; the snappers Lutjanus argentiventris and L. novemfasciatus; and the milkfish Chanos chanos (Sepúlveda-Medina 1981, Amezcua andPortillo 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results coincide with those recorded for the family Paralichthyidae and the genus Citharichthys in previous research (Vargas et al, 1999;Flores et al, 2013), which also found polychaetes to be important prey items. In this sense, some studies have shown that smaller flounder species, such as that examined in this case, are principally characterized as eaters of crabs (Labbé and Arana, 2001;Amezcua and Portillo, 2010) in contrast to larger species, which include an equal or greater percentage of fish among their principal prey (Latour et al, 2008).…”
Section: Trophic Habits and Feeding Strategiesmentioning
confidence: 94%
“…In addition, the way in which fish feed produces an exchange of materials and energy within the trophic web, thereby sustaining an ecological niche in the ecosystem (Guevara et al, 2007). For this reason, an understanding of trophic ecology provides important information on the dynamics and structure of the community (Cogua et al, 2013), making it possible to mitigate and counter the potential impacts to which a community might be susceptible (Amezcua and Portillo, 2010). Fish of the Paralichthyidae family are lefteye flounders and generally found in coastal environments (Robertson and Allen, 2015), usually on ocean and estuarine bottoms (Lopez et al, 2014), where juvenile flounders encounter appropriate conditions to feed and grow (Flores et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Existen pocos trabajos de alimentación en pleuronectiformes (Amezcua y Portillo 2010; Amezcua et al 2010;Flores Ortega et al 2013). La gran mayoría tratan otros aspectos biológicos y ecológicos como son la edad y crecimiento, distribución y abundancia, o solo se limitan a mencionarlos en listados taxonómicos (Murakami y Amoka 1992; Aceves-Medina et al 2003;Khidir et al 2005;Rodiles-Hernández et al 2005;Rodríguez Ibarra 2006; Rojas y Zapata 2006; Rodríguez Romero et al 2008;Tobón-López et al 2008;López Martínez at al.…”
Section: Introductionunclassified